Founding a farm: the marking out of Klein Stockwell, Western Cape, South Africa - Malherbe, Gideon François (School of Architecture, Planning and Geomatics, 2018)
This dissertation is rooted in my pursuit of developing a site engagement method that can be applied to learn from any given site by studying its history and inherent spatial logic. The research focuses primarily on a typological study of rural space and resulted in an architectural language that evolved from and amplifies the specific tradition of building as observed at Stockwell Farm in the Western Cape. The research process started with the temporal charting of the seen and the unseen forces affecting a portion of earth. Earth as seen in this work is a living organism that supports a historic community of interdependent individuals whom all leave marks upon its surface. Marking the earth is a daily practice in the rural agrarian space of Stockwell where historic and contemporary markings agglomerate to form a rural artefact that is the by-product of necessity. Within this resulting dissonance a space of unexpected sublimity arises. This dissertation critically approaches the establishment of a new farm on a portion of earth that has seen minimal marking. The portion is conversed with in a language learnt from its parent farm, Stockwell, and uses that as the basis for a vernacular of precast and expedient boer maak 'n plan building processes. The portion is moulded, marked and embellished to produce a space of multiple thresholds that arouse the sublime. I have designed a petrol station, truck stop, restaurant, organic farm, assorted barns, guest lodging, place of reflection, private sanctuaries and winery. Ultimately, a collection of buildings is brought to life and bound together by the moving of earth.